Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1093/oxfordjournals.humrep.a019088
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis: Secretion of interleukin-6 by human endometriotic cells and regulation by proinflammatory cytokines and sex steroids

Abstract: Endometriosis is generally associated with an immunoinflammatory process that takes place in the peritoneal cavity of patients. Interleukin (IL)-6, a multifunctional cytokine involved in numerous immunological and proliferative processes, has been found at high concentrations in the peritoneal fluid of endometriosis patients. The purpose of this study was to investigate the ability of endometriotic cells to produce IL-y and to assess the regulation of its secretion by proinflammatory cytokines and sex steroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 0 publications
2
62
0
1
Order By: Relevance
“…IL-1 would have more pronounced effects on adhesion in endometriosis (Sillem et al 1999). Activation and recruitment of immune cells into endometriotic implants can be mediated by other secreted cytokines and chemokines such as MCP-1, RANTES, IL-6, and IL-8, which were found to be up-regulated by IL-1 in endometriotic cells (Akoum et al 1995(Akoum et al , 1996(Akoum et al , 2002) and could in turn promote IL-1 secretion by activated immune cells. IL-1 induces secretion of IL-8 and IL-6, which exhibit proangiogenic properties (Akoum et al 1996.…”
Section: Il-1ri Expression In Ectopic Endometrial Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…IL-1 would have more pronounced effects on adhesion in endometriosis (Sillem et al 1999). Activation and recruitment of immune cells into endometriotic implants can be mediated by other secreted cytokines and chemokines such as MCP-1, RANTES, IL-6, and IL-8, which were found to be up-regulated by IL-1 in endometriotic cells (Akoum et al 1995(Akoum et al , 1996(Akoum et al , 2002) and could in turn promote IL-1 secretion by activated immune cells. IL-1 induces secretion of IL-8 and IL-6, which exhibit proangiogenic properties (Akoum et al 1996.…”
Section: Il-1ri Expression In Ectopic Endometrial Tissuementioning
confidence: 99%
“…Activation and recruitment of immune cells into endometriotic implants can be mediated by other secreted cytokines and chemokines such as MCP-1, RANTES, IL-6, and IL-8, which were found to be up-regulated by IL-1 in endometriotic cells (Akoum et al 1995(Akoum et al , 1996(Akoum et al , 2002) and could in turn promote IL-1 secretion by activated immune cells. IL-1 induces secretion of IL-8 and IL-6, which exhibit proangiogenic properties (Akoum et al 1996. Data from Lebovic et al (2000) showed an enhanced production of angiogenic molecules such as vascular endothelial growth factor (VEGF) and IL-6 in response to IL-1b in endometriotic cells, as compared with endometrial cells from normal endometrium, and increased expression of IL-1RI mRNA, suggesting a role for IL-1b ligand binding and signaling via IL-1RI.…”
Section: Il-1ri Expression In Ectopic Endometrial Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…The cytokine, which appears to mediate numerous physiologic and pathogenic processes, acts on a wide variety of cells and regulated immune responses, acute-phase responses of the liver, hematopoiesis, neuronal functions, and osteoclastogenesis (21). The cytokine may also have important functions in reproductive physiology, including the regulation of ovarian steroid production, folliculogenesis, and early events related to implantation (22,23). The fact that I L-6 is positively correlated with BDR may explain in part, why some hydrosalpingeal fluid samples are not embryotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 may also have important functions in reproductive physiology, including the regulation of ovarian steroid production, folliculogenesis and early events related to implantation. (Jacobs et al,1992); (Akoum et al, 1996). Both eutopic and ectopic endometrium are known to produce IL-6 .…”
Section: Cytokines and Pathogenesis Of Endometriosismentioning
confidence: 99%